Effect of quinoa (Chenopodium quinoa W.) flour supplementation in breads on the lipid profile and glycemic index: an in vivo study - Marak, Natasha R.; Das, Pranati; Das Purkayastha, Manashi; Baruah, Luna Dutta (Frontiers in Nutrition, 2024)
Quinoa is a gluten-free pseudocereal, with an excellent nutrient profile containing considerable amounts of fibre and minerals and rich in antioxidants such as polyphenols. The purpose of this research was to investigate the effects of quinoa bread on physical, chemical, bioactive components, glycaemic index and biochemical parameters. Human subjects aged between 20-50 years with absence of morbid factors were fed daily with quinoa bread for 3 months in order to study its pre-and post treatment effects on blood glucose, glycosylated haemoglobin and lipid profile. Effort was made to incorporate maximum amount of quinoa into the bread without compromising the acceptability of the bread. Out of the 14 formulations, TQ13, containing 20% quinoa flour with 3% wheat bran was selected for further analysis. The glycaemic index (GI) study revealed that quinoa bread peaked at 45 minutes with a gradual increase after ingestion of the bread and a steady decline thereafter. The observed value for blood glucose levels, before and after supplementation with quinoa incorporated bread was 86.96±15.32mg/dl and 84.25±18.26mg/dl respectively. There was a statistically significant (p≤0.05) decrease in levels of triglycerides, total cholesterol, low density lipoprotein (LDL) and very low density lipoprotein (VLDL) level before and after supplementation. However, nonsignificant changes were observed for high density lipoprotein (HDL) level from the pre-and post-treatment with the quinoa incorporated bread. Quinoa incorporated bread possessed low GI (42.00±0.83) compared to control (69.20±1.84) and long term consumption proved to contain functional efficacies in terms of hypolipidemic effect.